2014
DOI: 10.4103/2277-9175.145690
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum neutrophil gelatinase associated lipocalin with disease severity in hypertensive disorders of pregnancy

Abstract: Background:Vascular endothelial dysfunction is considered central to the pathogenesis of hypertensive disorders of pregnancy (HDP). Serum level of neutrophil gelatinase-associated lipocalin (NGAL) is closely related to endothelial injury. The aim of this study was to examine the correlation of serum NGAL with disease severity in HDP.Materials and Methods:This prospective case-control study was carried out for one year. After informed consent, ethical clearance, total 1,850 pregnant women were screened. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…They also evaluated urine NGAL levels and found no difference between preeclampsia and control groups. D'Anna et al (13), Stepan et al (19), Artunc-Ulkumen et al (24) and Sachan et al (25) detected that NGAL had a positive correlation with systolic and diastolic blood pressure, in accordance with results of our study. D'Anna et al (13,15) observed that serum NGAL had a positive correlation with proteinuria in preeclampsia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They also evaluated urine NGAL levels and found no difference between preeclampsia and control groups. D'Anna et al (13), Stepan et al (19), Artunc-Ulkumen et al (24) and Sachan et al (25) detected that NGAL had a positive correlation with systolic and diastolic blood pressure, in accordance with results of our study. D'Anna et al (13,15) observed that serum NGAL had a positive correlation with proteinuria in preeclampsia.…”
Section: Discussionsupporting
confidence: 91%
“…Sachan et al (25) have shown that serum NGAL was increased in women with preeclampsia compared to the controls, in women with eclampsia compared to severe preeclampsia, in women with severe preeclampsia compared to the women with mild preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 found that urinary NGAL concentrations of 110 ng/mL were associated with a sensitivity of 88% and a specificity of 85% for the diagnosis of non-prerenal AKI in decompensated cirrhosis patients. NGAL is an independent predictor of irreversible kidney function injury, and thus might be independent of other commonly used risk factors for predicting patient mortality 21 . The present study also found that urinary NGAL levels were significantly higher in the group with AKI secondary to decompensated cirrhosis than in the non-AKI and healthy control groups, and that urinary NGAL levels increased significantly with AKI progression.…”
Section: Discussionmentioning
confidence: 99%
“…For several decades, lots of biomarkers that can predict AKI were introduced to promptly initiate aggressive kidney-sparing and life-saving treatment [16]. These biomarkers mainly include kidney injury molecule-1 (KIM-1) [17], neutrophil gelatinase-associated lipocalin (NGAL) [18], and serum cystatin C (CYS-C) [19].…”
Section: Introductionmentioning
confidence: 99%